Impact of BDS-3 experimental satellites to BDS-2: Service area, precise products, precise positioning. Issue 4 (15th August 2018) - Zhang, Rui; Tu, Rui; Liu, Jinhai; Hong, Ju; Fan, Lihong; Zhang, Pengfei; Lu, Xiaochun
Abstract: Between 2015 and 2016, the BeiDou satellite navigation system (BDS) successfully launched 5 BeiDou global navigation satellite system experimental (BDS-3e) satellites. The number of available BDS satellites has increased. In this study, in order to analyze the impact of BDS-3e satellites on the current BDS, which is the BeiDou regional navigation satellite system (BDS-2), the number of visible satellites globally was used to analyze the influence of BDS-3e satellites on the service area of BDS. Then, based on the observations from May 3 to 11, 2017, the strategy of combined data processing of BDS-2 satellites and BDS-3e satellites is presented. Simultaneously, the orbits and clocks of BDS-2 satellites and BDS-3e satellites are calculated and their accuracy is analyzed. At last, based on the obtained orbits and clocks, the influence of BDS-3e satellites on the BDS precise positioning is initially analyzed. The results show that BDS-3e satellites can increase the number of visible satellites of BDS by 1 to 3 globally, thus increasing the service area of BDS. The accuracy of orbits and clocks of BDS-2 satellites and BDS-3e satellites determined by B1I and B3I signals satisfy the requirement of precise positioning. Furthermore, the participation of BDS-3e satellites improve the position dilution of precision (PDOP) value of positioning. The accuracy of precise point positioning (PPP) in the vertical component is significantly improved for tracking station in the low latitudes of the eastern hemisphere. According to multi-day statistics of a single tracking station, the accuracy of the static solution and the kinematic solution is improved by 64.7% and 25.6%, respectively. Moreover, the BDS-3e satellites significantly improve the accuracy of real-time kinematic (RTK) positioning for a medium baseline of 10 km. The E, N, and U components are improved by 5.6%, 14.3% and 7.7%, respectively.